Institutions that compete with library and information centres in th e provision of information services in Kampala Central division - Gershom, Willy Kato (Kampala: Makerere University, 1999)
Dissertation (DLIS) - Makerere University, 1999
Includes bibliographical references
Keywords: Libraries -- Information services; Museums -- Information services; Theatre -- Information services